A study of the growth and mobility of Pd nanoclusters on WO3(001) by scanning tunnelling microscopy - Dixon, R; Egdell, R (Elsevier, 2000)
The growth of Pd on WO3(001) at room temperature has been studied by scanning tunnelling microscopy. Thermally evaporated Pd grows on WO3(001) c(2 × 2) as truncated hemispherical nanoparticles whose mean diameter and height increase with increasing Pd coverage. There is some indication of preferential nucleation of clusters at step edges and at boundaries between c(2 × 2) and p(1 × 1) rafts on the (001) surface. Thermal annealing of nanoparticle covered surfaces at 873 K leads to agglomeration of the Pd clusters into large clumps with dimensions in excess of 10 nm, leaving bare terrace areas on the WO3(001) substrate with an increased proportion of reduced p(1 × 1) areas. The Pd nanoparticles are susceptible to tip induced movement, which can be used to sweep clusters out of a chosen area or to selectively remove individual clusters from a surface.